diff --git a/Basics.md b/Basics.md deleted file mode 100644 index 340a22da..00000000 --- a/Basics.md +++ /dev/null @@ -1,457 +0,0 @@ ---- -title : "Basics: Functional Programming in Agda" -layout : default -hide-implicit : false -extra-script : [agda-extra-script.html] -extra-style : [agda-extra-style.html] ---- - -
- -# Basics: Functional Programming in Agda - -The functional programming style brings programming closer to -simple, everyday mathematics: If a procedure or method has no side -effects, then (ignoring efficiency) all we need to understand -about it is how it maps inputs to outputs -- that is, we can think -of it as just a concrete method for computing a mathematical -function. This is one sense of the word "functional" in -"functional programming." The direct connection between programs -and simple mathematical objects supports both formal correctness -proofs and sound informal reasoning about program behavior. - -The other sense in which functional programming is "functional" is -that it emphasizes the use of functions (or methods) as -*first-class* values -- i.e., values that can be passed as -arguments to other functions, returned as results, included in -data structures, etc. The recognition that functions can be -treated as data in this way enables a host of useful and powerful -idioms. - -Other common features of functional languages include *algebraic -data types* and *pattern matching*, which make it easy to -construct and manipulate rich data structures, and sophisticated -*polymorphic type systems* supporting abstraction and code reuse. -Agda shares all of these features. - -This chapter introduces the most essential elements of Agda. - -## Enumerated Types - -One unusual aspect of Agda is that its set of built-in -features is *extremely* small. For example, instead of providing -the usual palette of atomic data types (booleans, integers, -strings, etc.), Agda offers a powerful mechanism for defining new -data types from scratch, from which all these familiar types arise -as instances. - -Naturally, the Agda distribution comes with an extensive standard -library providing definitions of booleans, numbers, and many -common data structures like lists and hash tables. But there is -nothing magic or primitive about these library definitions. To -illustrate this, we will explicitly recapitulate all the -definitions we need in this course, rather than just getting them -implicitly from the library. - -To see how this definition mechanism works, let's start with a -very simple example. - -### Days of the Week - -The following declaration tells Agda that we are defining -a new set of data values -- a *type*. - -- data Day : Set where - monday : Day - tuesday : Day - wednesday : Day - thursday : Day - friday : Day - saturday : Day - sunday : Day -- -The type is called `day`, and its members are `monday`, -`tuesday`, etc. The second and following lines of the definition -can be read "`monday` is a `day`, `tuesday` is a `day`, etc." - -Having defined `day`, we can write functions that operate on -days. - -
- nextWeekday : Day -> Day - nextWeekday monday = tuesday - nextWeekday tuesday = wednesday - nextWeekday wednesday = thursday - nextWeekday thursday = friday - nextWeekday friday = monday - nextWeekday saturday = monday - nextWeekday sunday = monday -- -One thing to note is that the argument and return types of -this function are explicitly declared. Like most functional -programming languages, Agda can often figure out these types for -itself when they are not given explicitly -- i.e., it performs -*type inference* -- but we'll include them to make reading -easier. - -Having defined a function, we should check that it works on -some examples. There are actually three different ways to do this -in Agda. - -First, we can use the Emacs command `C-c C-n` to evaluate a -compound expression involving `nextWeekday`. For instance, `nextWeekday -friday` should evaluate to `monday`. If you have a computer handy, this -would be an excellent moment to fire up Agda and try this for yourself. -Load this file, `Basics.lagda`, load it using `C-c C-l`, submit the -above example to Agda, and observe the result. - -Second, we can record what we *expect* the result to be in the -form of an Agda type: - -
- test_nextWeekday : nextWeekday (nextWeekday saturday) ≡ tuesday -- -This declaration does two things: it makes an assertion (that the second -weekday after `saturday` is `tuesday`), and it gives the assertion a name -that can be used to refer to it later. - -Having made the assertion, we must also verify it. We do this by giving -a term of the above type: - -
- test_nextWeekday = refl -- -There is no essential difference between the definition for -`test_nextWeekday` here and the definition for `nextWeekday` above, -except for the new symbol for equality `≡` and the constructor `refl`. -The details of these are not important for now (we'll come back to them in -a bit), but essentially `refl` can be read as "The assertion we've made -can be proved by observing that both sides of the equality evaluate to the -same thing, after some simplification." - -Third, we can ask Agda to *compile* some program involving our definition, -This facility is very interesting, since it gives us a way to construct -*fully certified* programs. We'll come back to this topic in later chapters. diff --git a/Maps.md b/Maps.md deleted file mode 100644 index 8902d3aa..00000000 --- a/Maps.md +++ /dev/null @@ -1,4467 +0,0 @@ ---- -title : "Maps: Total and Partial Maps" -layout : default -hide-implicit : false -extra-script : [agda-extra-script.html] -extra-style : [agda-extra-style.html] -permalink : "sf/Maps.html" ---- - -# Maps: Total and Partial Maps - -Maps (or dictionaries) are ubiquitous data structures, both in -software construction generally and in the theory of programming -languages in particular; we're going to need them in many places in -the coming chapters. They also make a nice case study using ideas -we've seen in previous chapters, including building data structures -out of higher-order functions (from [Basics](sf/Basics.html) -and [Poly](sf/Poly.html) and the use of reflection to streamline -proofs (from [IndProp](sf/IndProp.html). - -We'll define two flavors of maps: _total_ maps, which include a -"default" element to be returned when a key being looked up -doesn't exist, and _partial_ maps, which return an `Maybe` to -indicate success or failure. The latter is defined in terms of -the former, using `nothing` as the default element. - -## The Agda Standard Library - -One small digression before we start. - -Unlike the chapters we have seen so far, this one does not -import the chapter before it (and, transitively, all the -earlier chapters). Instead, in this chapter and from now, on -we're going to import the definitions and theorems we need -directly from Agda's standard library stuff. You should not notice -much difference, though, because we've been careful to name our -own definitions and theorems the same as their counterparts in the -standard library, wherever they overlap. - -
-open import Function using (_∘_) -open import Data.Bool using (Bool; true; false) -open import Data.Empty using (⊥; ⊥-elim) -open import Data.Maybe using (Maybe; just; nothing) -open import Data.Nat using (ℕ) -open import Relation.Nullary using (Dec; yes; no) -open import Relation.Binary.PropositionalEquality -- -Documentation for the standard library can be found at -
-data Id : Set where - id : ℕ → Id -- -
-_≟_ : (x y : Id) → Dec (x ≡ y) -id x ≟ id y with x Data.Nat.≟ y -id x ≟ id y | yes x=y rewrite x=y = yes refl -id x ≟ id y | no x≠y = no (x≠y ∘ id-inj) - where - id-inj : ∀ {x y} → id x ≡ id y → x ≡ y - id-inj refl = refl -- -## Total Maps - -Our main job in this chapter will be to build a definition of -partial maps that is similar in behavior to the one we saw in the -[Lists](sf/Lists.html) chapter, plus accompanying lemmas about their -behavior. - -This time around, though, we're going to use _functions_, rather -than lists of key-value pairs, to build maps. The advantage of -this representation is that it offers a more _extensional_ view of -maps, where two maps that respond to queries in the same way will -be represented as literally the same thing (the same function), -rather than just "equivalent" data structures. This, in turn, -simplifies proofs that use maps. - -We build partial maps in two steps. First, we define a type of -_total maps_ that return a default value when we look up a key -that is not present in the map. - -
-TotalMap : Set → Set -TotalMap A = Id → A -- -Intuitively, a total map over anfi element type $$A$$ _is_ just a -function that can be used to look up ids, yielding $$A$$s. - -
-module TotalMap where -- -The function `empty` yields an empty total map, given a -default element; this map always returns the default element when -applied to any id. - -
- empty : ∀ {A} → A → TotalMap A - empty x = λ _ → x -- -More interesting is the `update` function, which (as before) takes -a map $$m$$, a key $$x$$, and a value $$v$$ and returns a new map that -takes $$x$$ to $$v$$ and takes every other key to whatever $$m$$ does. - -
- update : ∀ {A} → TotalMap A -> Id -> A -> TotalMap A - update m x v y with x ≟ y - ... | yes x=y = v - ... | no x≠y = m y -- -This definition is a nice example of higher-order programming. -The `update` function takes a _function_ $$m$$ and yields a new -function $$\lambda x'.\vdots$$ that behaves like the desired map. - -For example, we can build a map taking ids to bools, where `id -3` is mapped to `true` and every other key is mapped to `false`, -like this: - -
- examplemap : TotalMap Bool - examplemap = update (update (empty false) (id 1) false) (id 3) true -- -This completes the definition of total maps. Note that we don't -need to define a `find` operation because it is just function -application! - -
- test_examplemap0 : examplemap (id 0) ≡ false - test_examplemap0 = refl - - test_examplemap1 : examplemap (id 1) ≡ false - test_examplemap1 = refl - - test_examplemap2 : examplemap (id 2) ≡ false - test_examplemap2 = refl - - test_examplemap3 : examplemap (id 3) ≡ true - test_examplemap3 = refl -- -To use maps in later chapters, we'll need several fundamental -facts about how they behave. Even if you don't work the following -exercises, make sure you thoroughly understand the statements of -the lemmas! (Some of the proofs require the functional -extensionality axiom, which is discussed in the [Logic] -chapter and included in the Agda standard library.) - -#### Exercise: 1 star, optional (apply-empty) -First, the empty map returns its default element for all keys: - -
- postulate - apply-empty : ∀ {A x v} → empty {A} v x ≡ v -- - - -#### Exercise: 2 stars, optional (update-eq) -Next, if we update a map $$m$$ at a key $$x$$ with a new value $$v$$ -and then look up $$x$$ in the map resulting from the `update`, we get -back $$v$$: - -
- postulate - update-eq : ∀ {A v} (m : TotalMap A) (x : Id) - → (update m x v) x ≡ v -- -
- update-eq′ : ∀ {A v} (m : TotalMap A) (x : Id) - → (update m x v) x ≡ v - update-eq′ m x with x ≟ x - ... | yes x=x = refl - ... | no x≠x = ⊥-elim (x≠x refl) --
- update-neq : ∀ {A v} (m : TotalMap A) (x y : Id) - → x ≢ y → (update m x v) y ≡ m y - update-neq m x y x≠y with x ≟ y - ... | yes x=y = ⊥-elim (x≠y x=y) - ... | no _ = refl -- -#### Exercise: 2 stars, optional (update-shadow) -If we update a map $$m$$ at a key $$x$$ with a value $$v_1$$ and then -update again with the same key $$x$$ and another value $$v_2$$, the -resulting map behaves the same (gives the same result when applied -to any key) as the simpler map obtained by performing just -the second `update` on $$m$$: - -
- postulate - update-shadow : ∀ {A v1 v2} (m : TotalMap A) (x y : Id) - → (update (update m x v1) x v2) y ≡ (update m x v2) y -- -
- update-shadow′ : ∀ {A v1 v2} (m : TotalMap A) (x y : Id) - → (update (update m x v1) x v2) y ≡ (update m x v2) y - update-shadow′ m x y - with x ≟ y - ... | yes x=y = refl - ... | no x≠y = update-neq m x y x≠y --
- postulate - update-same : ∀ {A} (m : TotalMap A) (x y : Id) - → (update m x (m x)) y ≡ m y -- -
- update-same′ : ∀ {A} (m : TotalMap A) (x y : Id) - → (update m x (m x)) y ≡ m y - update-same′ m x y - with x ≟ y - ... | yes x=y rewrite x=y = refl - ... | no x≠y = refl --
- postulate - update-permute : ∀ {A v1 v2} (m : TotalMap A) (x1 x2 y : Id) - → x1 ≢ x2 → (update (update m x2 v2) x1 v1) y - ≡ (update (update m x1 v1) x2 v2) y -- -
- update-permute′ : ∀ {A v1 v2} (m : TotalMap A) (x1 x2 y : Id) - → x1 ≢ x2 → (update (update m x2 v2) x1 v1) y - ≡ (update (update m x1 v1) x2 v2) y - update-permute′ {A} {v1} {v2} m x1 x2 y x1≠x2 - with x1 ≟ y | x2 ≟ y - ... | yes x1=y | yes x2=y = ⊥-elim (x1≠x2 (trans x1=y (sym x2=y))) - ... | no x1≠y | yes x2=y rewrite x2=y = update-eq′ m y - ... | yes x1=y | no x2≠y rewrite x1=y = sym (update-eq′ m y) - ... | no x1≠y | no x2≠y = - trans (update-neq m x2 y x2≠y) (sym (update-neq m x1 y x1≠y)) --
-PartialMap : Set → Set -PartialMap A = TotalMap (Maybe A) -- -
-module PartialMap where -- -
- empty : ∀ {A} → PartialMap A - empty = TotalMap.empty nothing -- -
- update : ∀ {A} (m : PartialMap A) (x : Id) (v : A) → PartialMap A - update m x v = TotalMap.update m x (just v) -- -We can now lift all of the basic lemmas about total maps to -partial maps. - -
- update-eq : ∀ {A v} (m : PartialMap A) (x : Id) - → (update m x v) x ≡ just v - update-eq m x = TotalMap.update-eq m x -- -
- update-neq : ∀ {A v} (m : PartialMap A) (x y : Id) - → x ≢ y → (update m x v) y ≡ m y - update-neq m x y x≠y = TotalMap.update-neq m x y x≠y -- -
- update-shadow : ∀ {A v1 v2} (m : PartialMap A) (x y : Id) - → (update (update m x v1) x v2) y ≡ (update m x v2) y - update-shadow m x y = TotalMap.update-shadow m x y -- -
- update-same : ∀ {A v} (m : PartialMap A) (x y : Id) - → m x ≡ just v - → (update m x v) y ≡ m y - update-same m x y mx=v rewrite sym mx=v = TotalMap.update-same m x y -- -
- update-permute : ∀ {A v1 v2} (m : PartialMap A) (x1 x2 y : Id) - → x1 ≢ x2 → (update (update m x2 v2) x1 v1) y - ≡ (update (update m x1 v1) x2 v2) y - update-permute m x1 x2 y x1≠x2 = TotalMap.update-permute m x1 x2 y x1≠x2 -diff --git a/README.md b/README.md index a3eb4a00..e69de29b 100644 --- a/README.md +++ b/README.md @@ -1 +0,0 @@ -# sf \ No newline at end of file diff --git a/Stlc.lagda b/Stlc.lagda index e754ad4b..2a347998 100644 --- a/Stlc.lagda +++ b/Stlc.lagda @@ -199,9 +199,9 @@ x = id 0 y = id 1 z = id 2 -{-# DISPLAY zero = x #-} -{-# DISPLAY suc zero = y #-} -{-# DISPLAY suc (suc zero) = z #-} +{-# DISPLAY id zero = x #-} +{-# DISPLAY id (suc zero) = y #-} +{-# DISPLAY id (suc (suc zero)) = z #-} \end{code} Some examples... @@ -246,6 +246,7 @@ notB = (abs x bool (if (var x) then false else true)) \end{code} + ## Operational Semantics To define the small-step semantics of STLC terms, we begin, diff --git a/Stlc.md b/Stlc.md deleted file mode 100644 index 3610cb48..00000000 --- a/Stlc.md +++ /dev/null @@ -1,5497 +0,0 @@ ---- -title : "Stlc: The Simply Typed Lambda-Calculus" -layout : default -hide-implicit : false -extra-script : [agda-extra-script.html] -extra-style : [agda-extra-style.html] -permalink : "sf/Stlc.html" ---- - -
-module Stlc where -- -
-open import Maps using (Id; id; _≟_; PartialMap; module PartialMap) -open import Data.Empty using (⊥; ⊥-elim) -open import Data.Maybe using (Maybe; just; nothing) -open import Data.Nat using (ℕ; suc; zero; _+_) -open import Data.Product using (∃; ∄; _,_) -open import Function using (_∘_; _$_) -open import Relation.Nullary using (Dec; yes; no) -open import Relation.Binary.PropositionalEquality using (_≡_; _≢_; refl) --
-data Type : Set where - bool : Type - _⇒_ : Type → Type → Type -- - - - -### Terms - -
-data Term : Set where - var : Id → Term - app : Term → Term → Term - abs : Id → Type → Term → Term - true : Term - false : Term - if_then_else_ : Term → Term → Term → Term -- - - -Note that an abstraction $$\lambda x:A.t$$ (formally, `abs x A t`) is -always annotated with the type $$A$$ of its parameter, in contrast -to Agda (and other functional languages like ML, Haskell, etc.), -which use _type inference_ to fill in missing annotations. We're -not considering type inference here. - -Some examples... - -
-x = id 0 -y = id 1 -z = id 2 -- - - -$$\text{idB} = \lambda x:bool. x$$. - -
-idB = (abs x bool (var x)) -- -$$\text{idBB} = \lambda x:bool\rightarrow bool. x$$. - -
-idBB = (abs x (bool ⇒ bool) (var x)) -- -$$\text{idBBBB} = \lambda x:(bool\rightarrow bool)\rightarrow (bool\rightarrow bool). x$$. - -
-idBBBB = (abs x ((bool ⇒ bool) ⇒ (bool ⇒ bool)) (var x)) -- -$$\text{k} = \lambda x:bool. \lambda y:bool. x$$. - -
-k = (abs x bool (abs y bool (var x))) -- -$$\text{notB} = \lambda x:bool. \text{if }x\text{ then }false\text{ else }true$$. - -
-notB = (abs x bool (if (var x) then false else true)) -- -
-{-# DISPLAY abs 0 bool (var 0) = idB #-} -{-# DISPLAY abs 0 (bool ⇒ bool) (var 0) = idBB #-} -{-# DISPLAY abs 0 ((bool ⇒ bool) ⇒ (bool ⇒ bool)) (var 0) = idBBBB #-} -{-# DISPLAY abs 0 bool (abs y bool (var 0)) = k #-} -{-# DISPLAY abs 0 bool (if (var 0) then false else true) = notB #-} --
-test_normalizeUnderLambda : (λ (x : ℕ) → 3 + 4) ≡ (λ (x : ℕ) → 7) -test_normalizeUnderLambda = refl -- -Most real-world functional programming languages make the second -choice---reduction of a function's body only begins when the -function is actually applied to an argument. We also make the -second choice here. - -
-data Value : Term → Set where - abs : ∀ {x A t} - → Value (abs x A t) - true : Value true - false : Value false -- -Finally, we must consider what constitutes a _complete_ program. - -Intuitively, a "complete program" must not refer to any undefined -variables. We'll see shortly how to define the _free_ variables -in a STLC term. A complete program is _closed_---that is, it -contains no free variables. - -Having made the choice not to reduce under abstractions, we don't -need to worry about whether variables are values, since we'll -always be reducing programs "from the outside in," and that means -the small-step relation will always be working with closed terms. - - -### Substitution - -Now we come to the heart of the STLC: the operation of -substituting one term for a variable in another term. This -operation is used below to define the operational semantics of -function application, where we will need to substitute the -argument term for the function parameter in the function's body. -For example, we reduce - -$$(\lambda x:bool. \text{if }x\text{ then }true\text{ else }x)\;false$$ - -to - -$$\text{if }false\text{ then }true\text{ else }false$$ - -by substituting $$false$$ for the parameter $$x$$ in the body of the -function. - -In general, we need to be able to substitute some given term $$s$$ -for occurrences of some variable $$x$$ in another term $$t$$. In -informal discussions, this is usually written $$[x:=s]t$$ and -pronounced "substitute $$x$$ with $$s$$ in $$t$$." - -Here are some examples: - - - $$[x:=true](\text{if }x\text{ then }x\text{ else }false)$$ - yields $$\text{if }true\text{ then }true\text{ else }false$$ - - - $$[x:=true]x$$ - yields $$true$$ - - - $$[x:=true](\text{if }x\text{ then }x\text{ else }y)$$ - yields $$\text{if }true\text{ then }true\text{ else }y$$ - - - $$[x:=true]y$$ - yields $$y$$ - - - $$[x:=true]false$$ - yields $$false$$ (vacuous substitution) - - - $$[x:=true](\lambda y:bool. \text{if }y\text{ then }x\text{ else }false)$$ - yields $$\lambda y:bool. \text{if }y\text{ then }true\text{ else }false$$ - - - $$[x:=true](\lambda y:bool. x)$$ - yields $$\lambda y:bool. true$$ - - - $$[x:=true](\lambda y:bool. y)$$ - yields $$\lambda y:bool. y$$ - - - $$[x:=true](\lambda x:bool. x)$$ - yields $$\lambda x:bool. x$$ - -The last example is very important: substituting $$x$$ with $$true$$ in -$$\lambda x:bool. x$$ does _not_ yield $$\lambda x:bool. true$$! The reason for -this is that the $$x$$ in the body of $$\lambda x:bool. x$$ is _bound_ by the -abstraction: it is a new, local name that just happens to be -spelled the same as some global name $$x$$. - -Here is the definition, informally... - -$$ - \begin{aligned} - &[x:=s]x &&= s \\ - &[x:=s]y &&= y \;\{\text{if }x\neq y\} \\ - &[x:=s](\lambda x:A. t) &&= \lambda x:A. t \\ - &[x:=s](\lambda y:A. t) &&= \lambda y:A. [x:=s]t \;\{\text{if }x\neq y\} \\ - &[x:=s](t1\;t2) &&= ([x:=s]t1) ([x:=s]t2) \\ - &[x:=s]true &&= true \\ - &[x:=s]false &&= false \\ - &[x:=s](\text{if }t1\text{ then }t2\text{ else }t3) &&= - \text{if }[x:=s]t1\text{ then }[x:=s]t2\text{ else }[x:=s]t3 - \end{aligned} -$$ - -... and formally: - -
-[_:=_]_ : Id -> Term -> Term -> Term -[ x := v ] (var y) with x ≟ y -... | yes x=y = v -... | no x≠y = var y -[ x := v ] (app s t) = app ([ x := v ] s) ([ x := v ] t) -[ x := v ] (abs y A t) with x ≟ y -... | yes x=y = abs y A t -... | no x≠y = abs y A ([ x := v ] t) -[ x := v ] true = true -[ x := v ] false = false -[ x := v ] (if s then t else u) = - if [ x := v ] s then [ x := v ] t else [ x := v ] u -- - - -_Technical note_: Substitution becomes trickier to define if we -consider the case where $$s$$, the term being substituted for a -variable in some other term, may itself contain free variables. -Since we are only interested here in defining the small-step relation -on closed terms (i.e., terms like $$\lambda x:bool. x$$ that include -binders for all of the variables they mention), we can avoid this -extra complexity here, but it must be dealt with when formalizing -richer languages. - - -#### Exercise: 3 stars (subst-correct) -The definition that we gave above defines substitution as a _function_. -Suppose, instead, we wanted to define substitution as an inductive _relation_. -We've begun the definition by providing the `data` header and -one of the constructors; your job is to fill in the rest of the constructors -and prove that the relation you've defined coincides with the function given -above. -
-data [_:=_]_==>_ (x : Id) (s : Term) : Term -> Term -> Set where - var1 : [ x := s ] (var x) ==> s - {- FILL IN HERE -} -- -
-postulate - subst-correct : ∀ s x t t' - → [ x := s ] t ≡ t' - → [ x := s ] t ==> t' -- - -### Reduction - -The small-step reduction relation for STLC now follows the -same pattern as the ones we have seen before. Intuitively, to -reduce a function application, we first reduce its left-hand -side (the function) until it becomes an abstraction; then we -reduce its right-hand side (the argument) until it is also a -value; and finally we substitute the argument for the bound -variable in the body of the abstraction. This last rule, written -informally as - -$$ -(\lambda x : A . t) v \Longrightarrow [x:=v]t -$$ - -is traditionally called "beta-reduction". - -$$ -\begin{array}{cl} - \frac{value(v)}{(\lambda x : A . t) v \Longrightarrow [x:=v]t}&(red)\\\\ - \frac{s \Longrightarrow s'}{s\;t \Longrightarrow s'\;t}&(app1)\\\\ - \frac{value(v)\quad t \Longrightarrow t'}{v\;t \Longrightarrow v\;t'}&(app2) -\end{array} -$$ - -... plus the usual rules for booleans: - -$$ -\begin{array}{cl} - \frac{}{(\text{if }true\text{ then }t_1\text{ else }t_2) \Longrightarrow t_1}&(iftrue)\\\\ - \frac{}{(\text{if }false\text{ then }t_1\text{ else }t_2) \Longrightarrow t_2}&(iffalse)\\\\ - \frac{s \Longrightarrow s'}{\text{if }s\text{ then }t_1\text{ else }t_2 - \Longrightarrow \text{if }s\text{ then }t_1\text{ else }t_2}&(if) -\end{array} -$$ - -Formally: - -
-data _==>_ : Term → Term → Set where - red : ∀ {x A s t} - → Value t - → app (abs x A s) t ==> [ x := t ] s - app1 : ∀ {s s' t} - → s ==> s' - → app s t ==> app s' t - app2 : ∀ {s t t'} - → Value s - → t ==> t' - → app s t ==> app s t' - if : ∀ {s s' t u} - → s ==> s' - → if s then t else u ==> if s' then t else u - iftrue : ∀ {s t} - → if true then s else t ==> s - iffalse : ∀ {s t} - → if false then s else t ==> t -- - - -
-data Multi (R : Term → Term → Set) : Term → Term → Set where - refl : ∀ {x} -> Multi R x x - step : ∀ {x y z} -> R x y -> Multi R y z -> Multi R x z -- -
-_==>*_ : Term → Term → Set -_==>*_ = Multi _==>_ -- - - -### Examples - -Example: - -$$((\lambda x:bool\rightarrow bool. x) (\lambda x:bool. x)) \Longrightarrow^* (\lambda x:bool. x)$$. - -
-step-example1 : (app idBB idB) ==>* idB -step-example1 = step (red abs) - $ refl -- -Example: - -$$(\lambda x:bool\rightarrow bool. x) \;((\lambda x:bool\rightarrow bool. x)\;(\lambda x:bool. x))) \Longrightarrow^* (\lambda x:bool. x)$$. - -
-step-example2 : (app idBB (app idBB idB)) ==>* idB -step-example2 = step (app2 abs (red abs)) - $ step (red abs) - $ refl -- -Example: - -$$((\lambda x:bool\rightarrow bool. x)\;(\lambda x:bool. \text{if }x\text{ then }false\text{ else }true))\;true\Longrightarrow^* false$$. - -
-step-example3 : (app (app idBB notB) true) ==>* false -step-example3 = step (app1 (red abs)) - $ step (red true) - $ step iftrue - $ refl -- -Example: - -$$((\lambda x:bool\rightarrow bool. x)\;((\lambda x:bool. \text{if }x\text{ then }false\text{ else }true)\;true))\Longrightarrow^* false$$. - -
-step-example4 : (app idBB (app notB true)) ==>* false -step-example4 = step (app2 abs (red true)) - $ step (app2 abs iftrue) - $ step (red false) - $ refl -- -#### Exercise: 2 stars (step-example5) - -
-postulate - step-example5 : (app (app idBBBB idBB) idB) ==>* idB -- -## Typing - -Next we consider the typing relation of the STLC. - -### Contexts - -_Question_: What is the type of the term "$$x\;y$$"? - -_Answer_: It depends on the types of $$x$$ and $$y$$! - -I.e., in order to assign a type to a term, we need to know -what assumptions we should make about the types of its free -variables. - -This leads us to a three-place _typing judgment_, informally -written $$\Gamma\vdash t : A$$, where $$\Gamma$$ is a -"typing context"---a mapping from variables to their types. - -Informally, we'll write $$\Gamma , x:A$$ for "extend the partial function -$$\Gamma$$ to also map $$x$$ to $$A$$." Formally, we use the function `_,_∶_` -(or "update") to add a binding to a context. - -
-Ctxt : Set -Ctxt = PartialMap Type - -∅ : Ctxt -∅ = PartialMap.empty - -_,_∶_ : Ctxt -> Id -> Type -> Ctxt -_,_∶_ = PartialMap.update -- - - - -### Typing Relation - -$$ - \begin{array}{cl} - \frac{\Gamma\;x = A}{\Gamma\vdash{x:A}}&(var)\\\\ - \frac{\Gamma,x:A\vdash t:B}{\Gamma\vdash (\lambda x:A.t) : A\rightarrow B}&(abs)\\\\ - \frac{\Gamma\vdash s:A\rightarrow B\quad\Gamma\vdash t:A}{\Gamma\vdash (s\;t) : B}&(app)\\\\ - \frac{}{\Gamma\vdash true : bool}&(true)\\\\ - \frac{}{\Gamma\vdash false : bool}&(true)\\\\ - \frac{\Gamma\vdash s:bool \quad \Gamma\vdash t1:A \quad \Gamma\vdash t2:A}{\Gamma\vdash\text{if }s\text{ then }t1\text{ else }t2 : A}&(if) - \end{array} -$$ - -We can read the three-place relation $$\Gamma\vdash (t : A)$$ as: -"to the term $$t$$ we can assign the type $$A$$ using as types for -the free variables of $$t$$ the ones specified in the context -$$\Gamma$$." - -
-data _⊢_∶_ : Ctxt -> Term -> Type -> Set where - var : ∀ {Γ} x {A} - → Γ x ≡ just A - → Γ ⊢ var x ∶ A - abs : ∀ {Γ} {x} {A} {B} {s} - → Γ , x ∶ A ⊢ s ∶ B - → Γ ⊢ abs x A s ∶ A ⇒ B - app : ∀ {Γ} {A} {B} {s} {t} - → Γ ⊢ s ∶ A ⇒ B - → Γ ⊢ t ∶ A - → Γ ⊢ app s t ∶ B - true : ∀ {Γ} - → Γ ⊢ true ∶ bool - false : ∀ {Γ} - → Γ ⊢ false ∶ bool - if_then_else_ : ∀ {Γ} {s} {t} {u} {A} - → Γ ⊢ s ∶ bool - → Γ ⊢ t ∶ A - → Γ ⊢ u ∶ A - → Γ ⊢ if s then t else u ∶ A -- - - - -### Examples - -
-typing-example1 : ∅ ⊢ idB ∶ bool ⇒ bool -typing-example1 = abs (var x refl) -- -Another example: - -$$\varnothing\vdash \lambda x:A. \lambda y:A\rightarrow A. y\;(y\;x) : A\rightarrow (A\rightarrow A)\rightarrow A$$. - -
-typing-example2 : ∅ ⊢ - (abs x bool - (abs y (bool ⇒ bool) - (app (var y) - (app (var y) (var x))))) - ∶ (bool ⇒ (bool ⇒ bool) ⇒ bool) -typing-example2 = - (abs - (abs - (app (var y refl) - (app (var y refl) (var x refl) )))) -- -#### Exercise: 2 stars (typing-example3) -Formally prove the following typing derivation holds: - -$$\exists A, \varnothing\vdash \lambda x:bool\rightarrow B. \lambda y:bool\rightarrow bool. \lambda z:bool. y\;(x\;z) : A$$. - -
-postulate - typing-example3 : ∃ λ A → ∅ ⊢ - (abs x (bool ⇒ bool) - (abs y (bool ⇒ bool) - (abs z bool - (app (var y) (app (var x) (var z)))))) ∶ A -- -We can also show that terms are _not_ typable. For example, let's -formally check that there is no typing derivation assigning a type -to the term $$\lambda x:bool. \lambda y:bool. x\;y$$---i.e., - - -$$\nexists A, \varnothing\vdash \lambda x:bool. \lambda y:bool. x\;y : A$$. - -
-postulate - typing-nonexample1 : ∄ λ A → ∅ ⊢ - (abs x bool - (abs y bool - (app (var x) (var y)))) ∶ A -- -#### Exercise: 3 stars, optional (typing-nonexample2) -Another nonexample: - -$$\nexists A, \exists B, \varnothing\vdash \lambda x:A. x\;x : B$$. - -
-postulate - typing-nonexample2 : ∄ λ A → ∃ λ B → ∅ ⊢ - (abs x B (app (var x) (var x))) ∶ A -diff --git a/StlcProp.md b/StlcProp.md deleted file mode 100644 index 9386c884..00000000 --- a/StlcProp.md +++ /dev/null @@ -1,5279 +0,0 @@ ---- -title : "StlcProp: Properties of STLC" -layout : default -hide-implicit : false -extra-script : [agda-extra-script.html] -extra-style : [agda-extra-style.html] -permalink : "sf/StlcProp.html" ---- - -
-module StlcProp where -- -
-open import Function using (_∘_) -open import Data.Empty using (⊥; ⊥-elim) -open import Data.Maybe using (Maybe; just; nothing) -open import Data.Product using (∃; ∃₂; _,_; ,_) -open import Data.Sum using (_⊎_; inj₁; inj₂) -open import Relation.Nullary using (¬_; Dec; yes; no) -open import Relation.Binary.PropositionalEquality using (_≡_; _≢_; refl) -open import Maps -open import Stlc --
-CanonicalForms : Term → Type → Set -CanonicalForms t bool = t ≡ true ⊎ t ≡ false -CanonicalForms t (A ⇒ B) = ∃₂ λ x t′ → t ≡ abs x A t′ - -canonicalForms : ∀ {t A} → ∅ ⊢ t ∶ A → Value t → CanonicalForms t A -canonicalForms (abs t′) abs = _ , _ , refl -canonicalForms true true = inj₁ refl -canonicalForms false false = inj₂ refl -- -## Progress - -As before, the _progress_ theorem tells us that closed, well-typed -terms are not stuck: either a well-typed term is a value, or it -can take a reduction step. The proof is a relatively -straightforward extension of the progress proof we saw in the -[Stlc](Stlc.html) chapter. We'll give the proof in English first, -then the formal version. - -
-progress : ∀ {t A} → ∅ ⊢ t ∶ A → Value t ⊎ ∃ λ t′ → t ==> t′ -- -_Proof_: By induction on the derivation of $$\vdash t : A$$. - - - The last rule of the derivation cannot be `var`, - since a variable is never well typed in an empty context. - - - The `true`, `false`, and `abs` cases are trivial, since in - each of these cases we can see by inspecting the rule that $$t$$ - is a value. - - - If the last rule of the derivation is `app`, then $$t$$ has the - form $$t_1\;t_2$$ for som e$$t_1$$ and $$t_2$$, where we know that - $$t_1$$ and $$t_2$$ are also well typed in the empty context; in particular, - there exists a type $$B$$ such that $$\vdash t_1 : A\to T$$ and - $$\vdash t_2 : B$$. By the induction hypothesis, either $$t_1$$ is a - value or it can take a reduction step. - - - If $$t_1$$ is a value, then consider $$t_2$$, which by the other - induction hypothesis must also either be a value or take a step. - - - Suppose $$t_2$$ is a value. Since $$t_1$$ is a value with an - arrow type, it must be a lambda abstraction; hence $$t_1\;t_2$$ - can take a step by `red`. - - - Otherwise, $$t_2$$ can take a step, and hence so can $$t_1\;t_2$$ - by `app2`. - - - If $$t_1$$ can take a step, then so can $$t_1 t_2$$ by `app1`. - - - If the last rule of the derivation is `if`, then $$t = \text{if }t_1 - \text{ then }t_2\text{ else }t_3$$, where $$t_1$$ has type $$bool$$. By - the IH, $$t_1$$ either is a value or takes a step. - - - If $$t_1$$ is a value, then since it has type $$bool$$ it must be - either $$true$$ or $$false$$. If it is $$true$$, then $$t$$ steps - to $$t_2$$; otherwise it steps to $$t_3$$. - - - Otherwise, $$t_1$$ takes a step, and therefore so does $$t$$ (by `if`). - -
-progress (var x ()) -progress true = inj₁ true -progress false = inj₁ false -progress (abs t∶A) = inj₁ abs -progress (app t₁∶A⇒B t₂∶B) - with progress t₁∶A⇒B -... | inj₂ (_ , t₁⇒t₁′) = inj₂ (_ , app1 t₁⇒t₁′) -... | inj₁ v₁ - with progress t₂∶B -... | inj₂ (_ , t₂⇒t₂′) = inj₂ (_ , app2 v₁ t₂⇒t₂′) -... | inj₁ v₂ - with canonicalForms t₁∶A⇒B v₁ -... | (_ , _ , refl) = inj₂ (_ , red v₂) -progress (if t₁∶bool then t₂∶A else t₃∶A) - with progress t₁∶bool -... | inj₂ (_ , t₁⇒t₁′) = inj₂ (_ , if t₁⇒t₁′) -... | inj₁ v₁ - with canonicalForms t₁∶bool v₁ -... | inj₁ refl = inj₂ (_ , iftrue) -... | inj₂ refl = inj₂ (_ , iffalse) -- -#### Exercise: 3 stars, optional (progress_from_term_ind) -Show that progress can also be proved by induction on terms -instead of induction on typing derivations. - -
-postulate - progress′ : ∀ {t A} → ∅ ⊢ t ∶ A → Value t ⊎ ∃ λ t′ → t ==> t′ -- -## Preservation - -The other half of the type soundness property is the preservation -of types during reduction. For this, we need to develop some -technical machinery for reasoning about variables and -substitution. Working from top to bottom (from the high-level -property we are actually interested in to the lowest-level -technical lemmas that are needed by various cases of the more -interesting proofs), the story goes like this: - - - The _preservation theorem_ is proved by induction on a typing - derivation, pretty much as we did in the [Stlc](Stlc.html) - chapter. The one case that is significantly different is the - one for the $$red$$ rule, whose definition uses the substitution - operation. To see that this step preserves typing, we need to - know that the substitution itself does. So we prove a... - - - _substitution lemma_, stating that substituting a (closed) - term $$s$$ for a variable $$x$$ in a term $$t$$ preserves the type - of $$t$$. The proof goes by induction on the form of $$t$$ and - requires looking at all the different cases in the definition - of substitition. This time, the tricky cases are the ones for - variables and for function abstractions. In both cases, we - discover that we need to take a term $$s$$ that has been shown - to be well-typed in some context $$\Gamma$$ and consider the same - term $$s$$ in a slightly different context $$\Gamma'$$. For this - we prove a... - - - _context invariance_ lemma, showing that typing is preserved - under "inessential changes" to the context $$\Gamma$$ -- in - particular, changes that do not affect any of the free - variables of the term. And finally, for this, we need a - careful definition of... - - - the _free variables_ of a term -- i.e., those variables - mentioned in a term and not in the scope of an enclosing - function abstraction binding a variable of the same name. - -To make Agda happy, we need to formalize the story in the opposite -order... - - -### Free Occurrences - -A variable $$x$$ _appears free in_ a term _t_ if $$t$$ contains some -occurrence of $$x$$ that is not under an abstraction labeled $$x$$. -For example: - - - $$y$$ appears free, but $$x$$ does not, in $$\lambda x : A\to B. x\;y$$ - - both $$x$$ and $$y$$ appear free in $$(\lambda x:A\to B. x\;y) x$$ - - no variables appear free in $$\lambda x:A\to B. \lambda y:A. x\;y$$ - -Formally: - -
-data _FreeIn_ (x : Id) : Term → Set where - var : x FreeIn var x - abs : ∀ {y A t} → y ≢ x → x FreeIn t → x FreeIn abs y A t - app1 : ∀ {t₁ t₂} → x FreeIn t₁ → x FreeIn app t₁ t₂ - app2 : ∀ {t₁ t₂} → x FreeIn t₂ → x FreeIn app t₁ t₂ - if1 : ∀ {t₁ t₂ t₃} → x FreeIn t₁ → x FreeIn (if t₁ then t₂ else t₃) - if2 : ∀ {t₁ t₂ t₃} → x FreeIn t₂ → x FreeIn (if t₁ then t₂ else t₃) - if3 : ∀ {t₁ t₂ t₃} → x FreeIn t₃ → x FreeIn (if t₁ then t₂ else t₃) -- -A term in which no variables appear free is said to be _closed_. - -
-Closed : Term → Set -Closed t = ∀ {x} → ¬ (x FreeIn t) -- -#### Exercise: 1 star (free-in) -If the definition of `_FreeIn_` is not crystal clear to -you, it is a good idea to take a piece of paper and write out the -rules in informal inference-rule notation. (Although it is a -rather low-level, technical definition, understanding it is -crucial to understanding substitution and its properties, which -are really the crux of the lambda-calculus.) - -### Substitution -To prove that substitution preserves typing, we first need a -technical lemma connecting free variables and typing contexts: If -a variable $$x$$ appears free in a term $$t$$, and if we know $$t$$ is -well typed in context $$\Gamma$$, then it must be the case that -$$\Gamma$$ assigns a type to $$x$$. - -
-freeInCtxt : ∀ {x t A Γ} → x FreeIn t → Γ ⊢ t ∶ A → ∃ λ B → Γ x ≡ just B -- -_Proof_: We show, by induction on the proof that $$x$$ appears - free in $$t$$, that, for all contexts $$\Gamma$$, if $$t$$ is well - typed under $$\Gamma$$, then $$\Gamma$$ assigns some type to $$x$$. - - - If the last rule used was `var`, then $$t = x$$, and from - the assumption that $$t$$ is well typed under $$\Gamma$$ we have - immediately that $$\Gamma$$ assigns a type to $$x$$. - - - If the last rule used was `app1`, then $$t = t_1\;t_2$$ and $$x$$ - appears free in $$t_1$$. Since $$t$$ is well typed under $$\Gamma$$, - we can see from the typing rules that $$t_1$$ must also be, and - the IH then tells us that $$\Gamma$$ assigns $$x$$ a type. - - - Almost all the other cases are similar: $$x$$ appears free in a - subterm of $$t$$, and since $$t$$ is well typed under $$\Gamma$$, we - know the subterm of $$t$$ in which $$x$$ appears is well typed - under $$\Gamma$$ as well, and the IH gives us exactly the - conclusion we want. - - - The only remaining case is `abs`. In this case $$t = - \lambda y:A.t'$$, and $$x$$ appears free in $$t'$$; we also know that - $$x$$ is different from $$y$$. The difference from the previous - cases is that whereas $$t$$ is well typed under $$\Gamma$$, its - body $$t'$$ is well typed under $$(\Gamma, y:A)$$, so the IH - allows us to conclude that $$x$$ is assigned some type by the - extended context $$(\Gamma, y:A)$$. To conclude that $$\Gamma$$ - assigns a type to $$x$$, we appeal the decidable equality for names - `_≟_`, noting that $$x$$ and $$y$$ are different variables. - -
-freeInCtxt var (var _ x∶A) = (_ , x∶A) -freeInCtxt (app1 x∈t₁) (app t₁∶A _ ) = freeInCtxt x∈t₁ t₁∶A -freeInCtxt (app2 x∈t₂) (app _ t₂∶A) = freeInCtxt x∈t₂ t₂∶A -freeInCtxt (if1 x∈t₁) (if t₁∶A then _ else _ ) = freeInCtxt x∈t₁ t₁∶A -freeInCtxt (if2 x∈t₂) (if _ then t₂∶A else _ ) = freeInCtxt x∈t₂ t₂∶A -freeInCtxt (if3 x∈t₃) (if _ then _ else t₃∶A) = freeInCtxt x∈t₃ t₃∶A -freeInCtxt {x} (abs {y} y≠x x∈t) (abs t∶B) - with freeInCtxt x∈t t∶B -... | x∶A - with y ≟ x -... | yes y=x = ⊥-elim (y≠x y=x) -... | no _ = x∶A -- -Next, we'll need the fact that any term $$t$$ which is well typed in -the empty context is closed (it has no free variables). - -#### Exercise: 2 stars, optional (∅⊢-closed) - -
-postulate - ∅⊢-closed : ∀ {t A} → ∅ ⊢ t ∶ A → Closed t -- -
-∅⊢-closed′ : ∀ {t A} → ∅ ⊢ t ∶ A → Closed t -∅⊢-closed′ (var x ()) -∅⊢-closed′ (app t₁∶A⇒B t₂∶A) (app1 x∈t₁) = ∅⊢-closed′ t₁∶A⇒B x∈t₁ -∅⊢-closed′ (app t₁∶A⇒B t₂∶A) (app2 x∈t₂) = ∅⊢-closed′ t₂∶A x∈t₂ -∅⊢-closed′ true () -∅⊢-closed′ false () -∅⊢-closed′ (if t₁∶bool then t₂∶A else t₃∶A) (if1 x∈t₁) = ∅⊢-closed′ t₁∶bool x∈t₁ -∅⊢-closed′ (if t₁∶bool then t₂∶A else t₃∶A) (if2 x∈t₂) = ∅⊢-closed′ t₂∶A x∈t₂ -∅⊢-closed′ (if t₁∶bool then t₂∶A else t₃∶A) (if3 x∈t₃) = ∅⊢-closed′ t₃∶A x∈t₃ -∅⊢-closed′ (abs {x = x} t′∶A) {y} (abs x≠y y∈t′) with freeInCtxt y∈t′ t′∶A -∅⊢-closed′ (abs {x = x} t′∶A) {y} (abs x≠y y∈t′) | A , y∶A with x ≟ y -∅⊢-closed′ (abs {x = x} t′∶A) {y} (abs x≠y y∈t′) | A , y∶A | yes x=y = x≠y x=y -∅⊢-closed′ (abs {x = x} t′∶A) {y} (abs x≠y y∈t′) | A , () | no _ --
-replaceCtxt : ∀ {Γ Γ′ t A} - → (∀ {x} → x FreeIn t → Γ x ≡ Γ′ x) - → Γ ⊢ t ∶ A - → Γ′ ⊢ t ∶ A -- -_Proof_: By induction on the derivation of -$$\Gamma \vdash t \in T$$. - - - If the last rule in the derivation was `var`, then $$t = x$$ - and $$\Gamma x = T$$. By assumption, $$\Gamma' x = T$$ as well, and - hence $$\Gamma' \vdash t : T$$ by `var`. - - - If the last rule was `abs`, then $$t = \lambda y:A. t'$$, with - $$T = A\to B$$ and $$\Gamma, y : A \vdash t' : B$$. The - induction hypothesis is that, for any context $$\Gamma''$$, if - $$\Gamma, y:A$$ and $$\Gamma''$$ assign the same types to all the - free variables in $$t'$$, then $$t'$$ has type $$B$$ under - $$\Gamma''$$. Let $$\Gamma'$$ be a context which agrees with - $$\Gamma$$ on the free variables in $$t$$; we must show - $$\Gamma' \vdash \lambda y:A. t' : A\to B$$. - - By $$abs$$, it suffices to show that $$\Gamma', y:A \vdash t' : t'$$. - By the IH (setting $$\Gamma'' = \Gamma', y:A$$), it suffices to show - that $$\Gamma, y:A$$ and $$\Gamma', y:A$$ agree on all the variables - that appear free in $$t'$$. - - Any variable occurring free in $$t'$$ must be either $$y$$ or - some other variable. $$\Gamma, y:A$$ and $$\Gamma', y:A$$ - clearly agree on $$y$$. Otherwise, note that any variable other - than $$y$$ that occurs free in $$t'$$ also occurs free in - $$t = \lambda y:A. t'$$, and by assumption $$\Gamma$$ and - $$\Gamma'$$ agree on all such variables; hence so do $$\Gamma, y:A$$ and - $$\Gamma', y:A$$. - - - If the last rule was `app`, then $$t = t_1\;t_2$$, with - $$\Gamma \vdash t_1 : A\to T$$ and $$\Gamma \vdash t_2 : A$$. - One induction hypothesis states that for all contexts $$\Gamma'$$, - if $$\Gamma'$$ agrees with $$\Gamma$$ on the free variables in $$t_1$$, - then $$t_1$$ has type $$A\to T$$ under $$\Gamma'$$; there is a similar IH - for $$t_2$$. We must show that $$t_1\;t_2$$ also has type $$T$$ under - $$\Gamma'$$, given the assumption that $$\Gamma'$$ agrees with - $$\Gamma$$ on all the free variables in $$t_1\;t_2$$. By `app`, it - suffices to show that $$t_1$$ and $$t_2$$ each have the same type - under $$\Gamma'$$ as under $$\Gamma$$. But all free variables in - $$t_1$$ are also free in $$t_1\;t_2$$, and similarly for $$t_2$$; - hence the desired result follows from the induction hypotheses. - -
-replaceCtxt f (var x x∶A) rewrite f var = var x x∶A -replaceCtxt f (app t₁∶A⇒B t₂∶A) - = app (replaceCtxt (f ∘ app1) t₁∶A⇒B) (replaceCtxt (f ∘ app2) t₂∶A) -replaceCtxt {Γ} {Γ′} f (abs {.Γ} {x} {A} {B} {t′} t′∶B) - = abs (replaceCtxt f′ t′∶B) - where - f′ : ∀ {y} → y FreeIn t′ → (Γ , x ∶ A) y ≡ (Γ′ , x ∶ A) y - f′ {y} y∈t′ with x ≟ y - ... | yes _ = refl - ... | no x≠y = f (abs x≠y y∈t′) -replaceCtxt _ true = true -replaceCtxt _ false = false -replaceCtxt f (if t₁∶bool then t₂∶A else t₃∶A) - = if replaceCtxt (f ∘ if1) t₁∶bool - then replaceCtxt (f ∘ if2) t₂∶A - else replaceCtxt (f ∘ if3) t₃∶A -- -Now we come to the conceptual heart of the proof that reduction -preserves types -- namely, the observation that _substitution_ -preserves types. - -Formally, the so-called _Substitution Lemma_ says this: Suppose we -have a term $$t$$ with a free variable $$x$$, and suppose we've been -able to assign a type $$T$$ to $$t$$ under the assumption that $$x$$ has -some type $$U$$. Also, suppose that we have some other term $$v$$ and -that we've shown that $$v$$ has type $$U$$. Then, since $$v$$ satisfies -the assumption we made about $$x$$ when typing $$t$$, we should be -able to substitute $$v$$ for each of the occurrences of $$x$$ in $$t$$ -and obtain a new term that still has type $$T$$. - -_Lemma_: If $$\Gamma,x:U \vdash t : T$$ and $$\vdash v : U$$, then -$$\Gamma \vdash [x:=v]t : T$$. - -
-[:=]-preserves-⊢ : ∀ {Γ x A t v B} - → ∅ ⊢ v ∶ A - → Γ , x ∶ A ⊢ t ∶ B - → Γ , x ∶ A ⊢ [ x := v ] t ∶ B -- -One technical subtlety in the statement of the lemma is that -we assign $$v$$ the type $$U$$ in the _empty_ context -- in other -words, we assume $$v$$ is closed. This assumption considerably -simplifies the $$abs$$ case of the proof (compared to assuming -$$\Gamma \vdash v : U$$, which would be the other reasonable assumption -at this point) because the context invariance lemma then tells us -that $$v$$ has type $$U$$ in any context at all -- we don't have to -worry about free variables in $$v$$ clashing with the variable being -introduced into the context by $$abs$$. - -The substitution lemma can be viewed as a kind of "commutation" -property. Intuitively, it says that substitution and typing can -be done in either order: we can either assign types to the terms -$$t$$ and $$v$$ separately (under suitable contexts) and then combine -them using substitution, or we can substitute first and then -assign a type to $$ $$x:=v$$ t $$ -- the result is the same either -way. - -_Proof_: We show, by induction on $$t$$, that for all $$T$$ and -$$\Gamma$$, if $$\Gamma,x:U \vdash t : T$$ and $$\vdash v : U$$, then $$\Gamma -\vdash $$x:=v$$t : T$$. - - - If $$t$$ is a variable there are two cases to consider, - depending on whether $$t$$ is $$x$$ or some other variable. - - - If $$t = x$$, then from the fact that $$\Gamma, x:U \vdash x : - T$$ we conclude that $$U = T$$. We must show that $$$$x:=v$$x = - v$$ has type $$T$$ under $$\Gamma$$, given the assumption that - $$v$$ has type $$U = T$$ under the empty context. This - follows from context invariance: if a closed term has type - $$T$$ in the empty context, it has that type in any context. - - - If $$t$$ is some variable $$y$$ that is not equal to $$x$$, then - we need only note that $$y$$ has the same type under $$\Gamma, - x:U$$ as under $$\Gamma$$. - - - If $$t$$ is an abstraction $$\lambda y:T_11. t_12$$, then the IH tells us, - for all $$\Gamma'$$ and $$T'$$, that if $$\Gamma',x:U \vdash t_12 : T'$$ - and $$\vdash v : U$$, then $$\Gamma' \vdash $$x:=v$$t_12 : T'$$. - - The substitution in the conclusion behaves differently - depending on whether $$x$$ and $$y$$ are the same variable. - - First, suppose $$x = y$$. Then, by the definition of - substitution, $$[x:=v]t = t$$, so we just need to show $$\Gamma \vdash - t : T$$. But we know $$\Gamma,x:U \vdash t : T$$, and, since $$y$$ - does not appear free in $$\lambda y:T_11. t_12$$, the context invariance - lemma yields $$\Gamma \vdash t : T$$. - - Second, suppose $$x <> y$$. We know $$\Gamma,x:U,y:T_11 \vdash t_12 : - T_12$$ by inversion of the typing relation, from which - $$\Gamma,y:T_11,x:U \vdash t_12 : T_12$$ follows by the context - invariance lemma, so the IH applies, giving us $$\Gamma,y:T_11 \vdash - $$x:=v$$t_12 : T_12$$. By $$abs$$, $$\Gamma \vdash \lambda y:T_11. $$x:=v$$t_12 - : T_11→T_12$$, and by the definition of substitution (noting - that $$x <> y$$), $$\Gamma \vdash \lambda y:T_11. $$x:=v$$t_12 : T_11→T_12$$ as - required. - - - If $$t$$ is an application $$t_1 t_2$$, the result follows - straightforwardly from the definition of substitution and the - induction hypotheses. - - - The remaining cases are similar to the application case. - -One more technical note: This proof is a rare case where an -induction on terms, rather than typing derivations, yields a -simpler argument. The reason for this is that the assumption -$$update Gamma x U \vdash t : T$$ is not completely generic, in the -sense that one of the "slots" in the typing relation -- namely the -context -- is not just a variable, and this means that Agda's -native induction tactic does not give us the induction hypothesis -that we want. It is possible to work around this, but the needed -generalization is a little tricky. The term $$t$$, on the other -hand, _is_ completely generic. - -
-[:=]-preserves-⊢ {Γ} {x} v∶A (var y y∈Γ) with x ≟ y -... | yes x=y = {!!} -... | no x≠y = {!!} -[:=]-preserves-⊢ v∶A (abs t′∶B) = {!!} -[:=]-preserves-⊢ v∶A (app t₁∶A⇒B t₂∶A) = - app ([:=]-preserves-⊢ v∶A t₁∶A⇒B) ([:=]-preserves-⊢ v∶A t₂∶A) -[:=]-preserves-⊢ v∶A true = true -[:=]-preserves-⊢ v∶A false = false -[:=]-preserves-⊢ v∶A (if t₁∶bool then t₂∶B else t₃∶B) = - if [:=]-preserves-⊢ v∶A t₁∶bool - then [:=]-preserves-⊢ v∶A t₂∶B - else [:=]-preserves-⊢ v∶A t₃∶B -- - -### Main Theorem - -We now have the tools we need to prove preservation: if a closed -term $$t$$ has type $$T$$ and takes a step to $$t'$$, then $$t'$$ -is also a closed term with type $$T$$. In other words, the small-step -reduction relation preserves types. - -Theorem preservation : forall t t' T, - empty \vdash t : T → - t ==> t' → - empty \vdash t' : T. - -_Proof_: By induction on the derivation of $$\vdash t : T$$. - -- We can immediately rule out $$var$$, $$abs$$, $$T_True$$, and - $$T_False$$ as the final rules in the derivation, since in each of - these cases $$t$$ cannot take a step. - -- If the last rule in the derivation was $$app$$, then $$t = t_1 - t_2$$. There are three cases to consider, one for each rule that - could have been used to show that $$t_1 t_2$$ takes a step to $$t'$$. - - - If $$t_1 t_2$$ takes a step by $$Sapp1$$, with $$t_1$$ stepping to - $$t_1'$$, then by the IH $$t_1'$$ has the same type as $$t_1$$, and - hence $$t_1' t_2$$ has the same type as $$t_1 t_2$$. - - - The $$Sapp2$$ case is similar. - - - If $$t_1 t_2$$ takes a step by $$Sred$$, then $$t_1 = - \lambda x:T_11.t_12$$ and $$t_1 t_2$$ steps to $$$$x:=t_2$$t_12$$; the - desired result now follows from the fact that substitution - preserves types. - - - If the last rule in the derivation was $$if$$, then $$t = if t_1 - then t_2 else t_3$$, and there are again three cases depending on - how $$t$$ steps. - - - If $$t$$ steps to $$t_2$$ or $$t_3$$, the result is immediate, since - $$t_2$$ and $$t_3$$ have the same type as $$t$$. - - - Otherwise, $$t$$ steps by $$Sif$$, and the desired conclusion - follows directly from the induction hypothesis. - -Proof with eauto. - remember (@empty ty) as Gamma. - intros t t' T HT. generalize dependent t'. - induction HT; - intros t' HE; subst Gamma; subst; - try solve $$inversion HE; subst; auto$$. - - (* app - inversion HE; subst... - (* Most of the cases are immediate by induction, - and $$eauto$$ takes care of them - + (* Sred - apply substitution_preserves_typing with T_11... - inversion HT_1... -Qed. - -#### Exercise: 2 stars, recommended (subject_expansion_stlc) -An exercise in the $$Stlc$$$$sf/Stlc.html$$ chapter asked about the subject -expansion property for the simple language of arithmetic and -boolean expressions. Does this property hold for STLC? That is, -is it always the case that, if $$t ==> t'$$ and $$has_type t' T$$, -then $$empty \vdash t : T$$? If so, prove it. If not, give a -counter-example not involving conditionals. - -(* FILL IN HERE - -## Type Soundness - -#### Exercise: 2 stars, optional (type_soundness) -Put progress and preservation together and show that a well-typed -term can _never_ reach a stuck state. - -Definition stuck (t:tm) : Prop := - (normal_form step) t /\ ~ value t. - -Corollary soundness : forall t t' T, - empty \vdash t : T → - t ==>* t' → - ~(stuck t'). -Proof. - intros t t' T Hhas_type Hmulti. unfold stuck. - intros $$Hnf Hnot_val$$. unfold normal_form in Hnf. - induction Hmulti. - (* FILL IN HERE Admitted. -(** $$$$ - - -## Uniqueness of Types - -#### Exercise: 3 stars (types_unique) -Another nice property of the STLC is that types are unique: a -given term (in a given context) has at most one type. -Formalize this statement and prove it. - -(* FILL IN HERE -(** $$$$ - - -## Additional Exercises - -#### Exercise: 1 star (progress_preservation_statement) -Without peeking at their statements above, write down the progress -and preservation theorems for the simply typed lambda-calculus. -$$$$ - -#### Exercise: 2 stars (stlc_variation1) -Suppose we add a new term $$zap$$ with the following reduction rule - - --------- (ST_Zap) - t ==> zap - -and the following typing rule: - - ---------------- (T_Zap) - Gamma \vdash zap : T - -Which of the following properties of the STLC remain true in -the presence of these rules? For each property, write either -"remains true" or "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - - -#### Exercise: 2 stars (stlc_variation2) -Suppose instead that we add a new term $$foo$$ with the following -reduction rules: - - ----------------- (ST_Foo1) - (\lambda x:A. x) ==> foo - - ------------ (ST_Foo2) - foo ==> true - -Which of the following properties of the STLC remain true in -the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - -#### Exercise: 2 stars (stlc_variation3) -Suppose instead that we remove the rule $$Sapp1$$ from the $$step$$ -relation. Which of the following properties of the STLC remain -true in the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - -#### Exercise: 2 stars, optional (stlc_variation4) -Suppose instead that we add the following new rule to the -reduction relation: - - ---------------------------------- (ST_FunnyIfTrue) - (if true then t_1 else t_2) ==> true - -Which of the following properties of the STLC remain true in -the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - - - -#### Exercise: 2 stars, optional (stlc_variation5) -Suppose instead that we add the following new rule to the typing -relation: - - Gamma \vdash t_1 : bool→bool→bool - Gamma \vdash t_2 : bool - ------------------------------ (T_FunnyApp) - Gamma \vdash t_1 t_2 : bool - -Which of the following properties of the STLC remain true in -the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - - - -#### Exercise: 2 stars, optional (stlc_variation6) -Suppose instead that we add the following new rule to the typing -relation: - - Gamma \vdash t_1 : bool - Gamma \vdash t_2 : bool - --------------------- (T_FunnyApp') - Gamma \vdash t_1 t_2 : bool - -Which of the following properties of the STLC remain true in -the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - - - -#### Exercise: 2 stars, optional (stlc_variation7) -Suppose we add the following new rule to the typing relation -of the STLC: - - ------------------- (T_FunnyAbs) - \vdash \lambda x:bool.t : bool - -Which of the following properties of the STLC remain true in -the presence of this rule? For each one, write either -"remains true" or else "becomes false." If a property becomes -false, give a counterexample. - - - Determinism of $$step$$ - - - Progress - - - Preservation - - -### Exercise: STLC with Arithmetic - -To see how the STLC might function as the core of a real -programming language, let's extend it with a concrete base -type of numbers and some constants and primitive -operators. - -To types, we add a base type of natural numbers (and remove -booleans, for brevity). - -Inductive ty : Type := - | TArrow : ty → ty → ty - | TNat : ty. - -To terms, we add natural number constants, along with -successor, predecessor, multiplication, and zero-testing. - -Inductive tm : Type := - | tvar : id → tm - | tapp : tm → tm → tm - | tabs : id → ty → tm → tm - | tnat : nat → tm - | tsucc : tm → tm - | tpred : tm → tm - | tmult : tm → tm → tm - | tif0 : tm → tm → tm → tm. - -#### Exercise: 4 stars (stlc_arith) -Finish formalizing the definition and properties of the STLC extended -with arithmetic. Specifically: - - - Copy the whole development of STLC that we went through above (from - the definition of values through the Type Soundness theorem), and - paste it into the file at this point. - - - Extend the definitions of the $$subst$$ operation and the $$step$$ - relation to include appropriate clauses for the arithmetic operators. - - - Extend the proofs of all the properties (up to $$soundness$$) of - the original STLC to deal with the new syntactic forms. Make - sure Agda accepts the whole file.